Androgens and offending behavior: Evidence based on multiple self-reported measures of prenatal and general testosterone exposure - Hoskin, Anthony W. (Pergamon-Elsevier Science Ltd, 2021)
Using indications of testosterone exposure, such as 2D:4D, anogenital distance, muscularity and physical strength, and masculine-feminine appearances and mannerisms, this study tested the hypothesis that life-course exposure to testosterone promotes offending behavior. An online sample of 324 research participants was asked nine questions regarding testosterone-promoted traits. When correlations were performed for the sample as a whole, strong support was found for the hypothesis that exposure to testosterone promotes offending behavior, at least regarding aggressive and violent offenses. Results were weakened when the correlations were performed for males and females separately, especially regarding the two prenatal testosterone exposure variables (i.e., 2D:4D and anogenital distance). However, substantial support for the hypothesis remained for general testosterone-promoted traits (especially muscularity and physical strength for males, and masculine mannerisms for females). Overall, this study supports recent theories that brain exposure to testosterone could be contributing to variations in criminality, especially when violence is involved. The study also suggests that self-reported indicators or testosterone exposure may provide more reliable evidence for testosterone's influence on aggressive and violent behavior than do direct measures of testosterone in the blood or saliva following puberty.